Genetic variability and selection of high root yield and high eurycomanone content genotypes in Malaysian tongkat ali (Eurycoma longifolia Jack) germplasm - Govindasamy, Sentoor Kumeran (2014)
Eurycoma longifolia or better known as tongkat ali in Malaysia is a herb used mainly as general tonic, aphrodisiac and antipyretics. It belongs to the Simaroubaceae family and found mainly in lowland forest of Malaysia thriving under forest canopy. Currently, in Malaysia, the major supply of tongkat ali comes from wild collections of forest reserves. Over harvesting of wild tongkat ali cause extinction of the species. There were not many recorded information on the study of tongkat ali in the aspects of breeding, agronomic, pest and disease management, post harvest technology and bio-molecular assay in Malaysia. Thus, it is important to identify accessions of tongkat ali which exhibit high growth rate and good root yield in the germplasm collection for farmers use and cultivation. This will significantly reduce wild collections and increase cultivation of tongkat ali for industrial use. Among various parts of tongkat ali, the tap root of the plant appears to be in use greatly. In this study, 10 accessions of tongkat ali were collected from the forest of Peninsular Malaysia for evaluation of viability in non shade growing condition, growth and yield performance, chemical content analysis, genetic similarity, G × E interactions and heritability of traits. The accessions were planted in RCBD experimental design in three replicates at two locations, namely MARDI Serdang and MARDI Kluang. The height and girth data were collected at six month intervals. Beside, other morphological data such as internode length, leaf length, number of leaflets per leaf, leaflet area, leaflet width and length were taken during the final collection of height and girth data. Other parameters taken into consideration include yield data of total root yield, lateral and tap root yield and plant crown weight. In order to investigate on the DNA extraction of tongkat ali, leaflets samples were collected simultaneously during experimentation. Data collected were analyzed statistically using SAS procedures for Analysis of variance (ANOVA) and the New Duncan Multiple Range Test for progeny impact between treatments and locations. Molecular markers data were analyzed using NTSYS-pc 2.1 to generate genetic similarity cluster dendrogram. From the data collected on plant height and girth in Serdang and Kluang, significant differences among the accessions in terms of growth were observed. Among the accessions, the highest mean plant height obtained of MEL 10 was 355 cm in Serdang and 395 cm in Kluang. MEL 10 in Serdang and Kluang produced the biggest girth among the treatments with girth size of 68 mm and 72 mm respectively. Significant differences were obtained among the number of leaflets per leaf, leaf length and leaflet area in Serdang and number of leaflets, leaflet area, leaf length, leaflet width and tree crown weight in Kluang. Meanwhile, fresh root yield of tongkat ali in both locations exhibited significant variations among the 10 accessions of tongkat ali. MEL 08 in Serdang and Kluang showed highest root yield of tongkat ali. The analysis of G × E showed differences in genotypes performance in the two locations in term of height and girth size. Cluster analysis at 0.75 mean average distances among the accessions indicated the existence of four distinctive types of tongkat ali accessions among the collected 10 accessions using plant morphological characters analysis. Accession MEL 12 had the highest concentration of eurycomanone in the roots. Chemical content was a highly heritable trait as the broad-sense heritability values were above 70% in terms of eurycomanone content in tap root, lateral root and leaves. An IMP molecular marker assisted cluster analysis showed at 0.75 coefficient value, six distinctive clusters of tongkat ali among the 10 collected tongkat ali accessions.